Classification of Sedimentation Problems Level Using Environmetric Method at Terengganu River, Malaysia - Khairul Amri Kamarudin, Mohd; Abd Wahab, Noorjima; Ekhwan Toriman, Mohd; Marcus Ata, Frankie; Umar, Roslan; Yaakub, Nadzifah; Abdullah, Hanif; Anuar, Atikah; Rahman Hassan, Abdul; Shakir Mohd Saudi, Ahmad; Harith, Hazamri; Hairoma, Norsyuhada (International Journal of Engineering and Technology, 2018)
This study was implemented to prove the sedimentation problem. The technique of analysis of primary data obtained which determine according procedure Gravimetric method, Gerald & Kenneth and the scale Udden - Wentworth which included median, mean, standard deviation, skewness, and kurtosis. The results showed the highest average of TSS (mg/L) is 67.2 (wet season) and 128.2 (dry season). While the highest TUR is 43.57 (wet season) and 21.57 (dry season). The statistical analysis of the phi value obtained showed the size of sediment grains is dominated by the rough size (phi -0.10 to phi -0.30) and very rough (phi -0.30 to -1.00) which signify the production of sedimentation behavior. The statistical analysis proved the weak regression relationship between TSS, TUR, river discharge (Q) and skewness caused by the anthropogenic factors and uncertain climate changes. The Agglomerative Hierarchical Clustering (AHC) enabled to group 29 monitoring sites into a few groups (sand mining area, industrial and development of socioeconomic, agricultural and farming, residential and domestic waste). The contributors of sedimentation problems from unsustainable land use and climate changes which are effectively trapping the bed sediments, backflow that carries out high sediments.Â Â